Teaching CBT to Pre-Registration nurses: A critical account of a teaching session to pre-registration mental health nurses on the subject of cognitive behavioural therapy and trauma - Binnie, James (International Journal of Psychosocial Rehabilitation, 2018)
Purpose: The role of the mental health nurse is changing. Expectations of what nurses can and should be practising are increasing. Mental health nurses are often involved in delivering cognitive behavioural therapy (CBT). Usually these skills are taught after qualification. However, given the changing climate it is proposed that these skills are taught pre-registration. Approach: This paper reflects on a teaching session given to a group of pre-registration mental health nurses on the subject of CBT and trauma. The planning, delivery and evaluation of the session is de- scribed and recommendations are made. Findings: It is put forward that this paper demonstrates an overview of effective teaching based on sound pedagogical theory. Value: It is hoped that the reader will reflect on the wide scope for pre-registration training; in particular the role of CBT. The reader may also find the paper useful when considering their own teaching practice.